Development of selective laser melting process parameters for inconel 625 alloy - Prata, Inês Sousa (2021)
The aim of this work was to develop a Metal Additive Manufacturing technique, namely Selective Laser Melting (SLM), for the fabrication of Inconel 625 alloy components with the aim of improving productivity. The work done consisted in adapting and developing the process parameters of SLM to produce components for the automotive industry using 90 μm of layer thickness instead of 30 or 60 μm that were already know at HPE-COXA, where the internship was held. These parameters included the Laser Power, Scanning Speed and Hatch Distance in a DMG-MORI LaserTec 30 SLM equipment. Validation of SLM conditions were determined by set-up procedures of core, boundary, downskin, upskin and supports. The surface aspect and microstructure were analysed to validate the imposed parameters. The best compromise between all the parameters resulted on a sound component that was used to validate the geometrical stability during the additive manufacturing. Finally, a homologation job of the customer’s component was built, together with specimens to verify the tensile strength in xy-orientation and in the vertical axis, hardness, density and surface roughness, as specified by the costumer. The results showed that fabrication of the component with 90 μm layer thickness is now possible and in conditions that largely reduce the fabrication time, resulting in a productivity increased of 82%.